BLACK VIETNAM VETERAN, TRAUMA AND IDENTITY: ANALYSIS OF HISTORICAL TRAUMA IN SPIKE LEE’S DA 5 BLOODS - Renatawati, Reni; Munjid, Achmad (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
As part of the postnational study, this study aims to identify the trauma Black Vietnam veterans suffered in the present time and their stance as Americans in Da 5 Bloods. Using a qualitative method in collecting the primary data from the conversation that happened in the film, as well as finding secondary data from books, journal articles, and the internet related to the study to support the analysis, this study also used historical trauma theory by LaCapra to help define the meaning behind the conversation and construct a more comprehensive view on the traumatic aspect in history. Based on the discussion, this study finds that Black Vietnam veterans are still most likely to suffer from PTSD in the present time because of their mistrust toward the VA and other Vietnamese despite being an ally. At the same time, the experience Black Vietnam veterans had from serving their country thus defines their perspective toward the government and the US as a whole because of how they were and are treated. In the end, the experience from the war made their stance against the war and its cruelty become crystal clear.